Terrorism in Pakistan: A Non-Traditional Security Threat in the 21st Century - Raza, Ahmad; Zaman, Zumar; Mustafa, Ghulam (Annals of Human and Social Sciences, 2025)
The main objective of this study is to understand the challenges that terrorism poses to Pakistan’s security, governance, and socio-economic development. Terrorism is becoming one of the paramount’s Non-Traditional Security threats in Pakistan with special reference to 21st century that threatens the social, political & economic fabrics of the society. While traditional security threats are associated with interstate conflicts, terrorism derives from transnational ideas, political disorder within a country, and social and economic inequality within the national society. The Pakistanis, furthermore, national strategic placement and the country’s involvement in earlier global conflicts like the Afghanistan war has increase it seismic vulnerability. This has led to emergence of extreme groups, a tradition of sectarian violence and continued exploitation of open borders, putting into question the issue of security leading to a cycle of insecurity. This paper aims to identify the social, economic and political consequences of terrorism on the future of Pakistani Nation and its growth. They underpin the efforts the state has been making in its fight against terrorism using military force, legal frameworks and social-economic measures and more importantly focuses on the challenges of the implementation of policies. The study also points to the fact that there is a need for effective coordination between counter terrorism and development initiatives in order to deal with causes of conflict including poverty, illiteracy and bad governance. Besides, the study puts more emphasis on regional cooperation, as well as international cooperation in the fight against terrorism. Thus, this qualitative study is useful in the understanding of how non-traditional security threats transform the indicators of both national and regional security in the twenty first century.